Early Childhood Self-Efficacy in The Book "Alia Juga Berani" by Liza Erfiana - Ardhiny (International Proceedings of Nusantara Raya, 2024)
This research aims to examine the psychological factors important for early childhood development, namely self-confidence or self-efficacy. The purpose of this study is to analyze Self Efficacy in the book "Alia Also Brave" by Liza Erfiana. The method used is a qualitative approach with a type of descriptive qualitative research. Based on the research results, the level of self-confidence in early childhood in the book "Alia Also Brave" by Liza Erfiana tends to be good or has positive characteristics. This condition is evident from the research findings in the book "Alia Also Brave" by Liza Erfiana. The research findings can be seen at the end of the story where the student finds confidence in their abilities by bravely singing in front of the class. That feeling of self-confidence represents a sense of being accepted, a sense of capability, and a sense of worth that has not yet developed due to factors such as successful experiences, previous experiences, and also mood.